Swallowed dentures causing sigmoid perforation: a case report - Mochammad Junaidy Heriyanto; Triyoga Triyoga (Ahmad Dahlan Medical Journal, 2020)
We report the case of a 72-year-old man who accidentally swallowed his dental bridge. He did not realize his artificial teeth were swallowed. The patient was taken to the emergency room with complaints of abdominal pain. At the time of initial exploration, the patient was diagnosed with kidney colic. After a radiological examination, a foreign object was found. The patient undergoes laparotomy to evacuate a foreign body and find dentures. At the time of surgery, the operator observed the sigmoid perforation.Â